SCHOOL CANTEEN SERVICE MANAGEMENT AND STUDENT SATISFACTION: A QUALITATIVE STUDY - Nandalita Nunuela; Marsya Kwalomine; Febriyanti Kibas (CV. TOTUS TUUS, 2026)
This study describes the management of school canteen services at SMP Negeri 19 Ambon and examines how the service supports student satisfaction, food safety, nutritional awareness, and a healthy school environment. The study was motivated by the role of the school canteen as a special educational service that provides food and beverages while also functioning as a medium for health education, character formation, and social interaction among students. This research employed a qualitative descriptive design. Data were collected through direct observation of canteen facilities and service practices, semi-structured interviews with the school principal, canteen manager, teachers involved in supervision, school infrastructure personnel, and student representatives, as well as documentation of school policies and canteen-related records. Data were analyzed through data condensation, thematic categorization, data display, and conclusion drawing, supported by source and technique triangulation. The findings show that canteen management at SMP Negeri 19 Ambon has been implemented through basic planning, the formation of a supervisory team, daily food service operation, price control, and monitoring of food safety. Students generally expressed satisfaction with the affordability, taste, and accessibility of the food. However, several aspects still require improvement, including limited dining space, insufficient tables and chairs, occasional shortages of favorite menus, limited vegetable-based dishes, and the need for more systematic student feedback. The study concludes that the canteen has contributed positively to student welfare and school health culture, but its management should be strengthened through written service standards, menu diversification, facility improvement, nutrition education, and periodic evaluation of student satisfaction.